Data on full stationary wave-field measurement of a suspended steel plate punctually loadedMendeley Data - Xuefeng Li; Thomas Brion; Pascal Fossat; Mohamed Ichchou; Olivier Bareille; Abdel-Malek Zine (Data in Brief)
The dataset presented contains the experimental structural response, in the frequency domain, of a suspended steel plate to a point force excitation. The plate is excited by a mechanical point force generated by a Brüel & kJær shaker with a white noise signal input from 3.125 Hz to 2000 Hz. The out-of-plate displacement fields on a 2D grid were measured using a Polytec PSV-400 Scanning Vibrometer. Finally, the displacement fields are acquired by a Fourier analyser connected to a sampler. The dataset provided is a useful resource for researchers to study the structural dynamic behaviour of large thin plates in the frequency domain and to validate the effectiveness of wavenumber identification methods. Its value has been illustrated in the research paper “Algebraic K-Space Identification 2D technique for the automatic extraction of complex k-space of 2D structures in presence of uncertainty” [1]. The data collection was carried out during three weeks in April 2022 at the Ecole Central de Lyon.